RESISTENSI TOKOH UTAMA PEREMPUAN TERHADAP DOMINASI PATRIARKI DALAM SERIAL MUSIKAL NURBAYA (2021) - Pratama, Indra; Ratri Rahmiaji, Lintang; Lukmantoro, Triyono (Interaksi Online, 2024)
Gender inequality and patriarchal domination remain significant issues in Indonesia, including in the Minangkabau society, which follows a matrilineal kinship system. Despite the important role of women in Minangkabau's social structure, patriarchy still prevails, creating disparities between men and women. The Musikal Nurbaya (2021) series highlights this issue through its female protagonist who faces patriarchal pressure. This study aims to analyze the forms of resistance exhibited by the main female character against patriarchal domination in the series. Using hermeneutic analysis, the study explores 13 scenes and 3 songs in the series to understand how gender injustice is critiqued and confronted by the main character. The results show that the character Nur demonstrates both open and covert resistance to patriarchal domination, reflected in her rejection of traditional gender norms and her fight for individual freedom. The series also reveals that despite Minangkabau's matrilineal system, patriarchal domination continues to affect women's lives. In conclusion, Nur's resistance reflects a broader struggle to achieve gender equality amid patriarchal norms.